The effect of demonstration and mind mapping learning methods on achievement of cultural arts course - Jarmani, Jarmani; Rusijiono, Rusijiono; Bachri, Bachtiar Saiful; Suryarini, Diah Yovita (Universitas Malikussaleh, 2021)
This study has looked at the variations in cultural learning outcomes for groups of students that utilize the methods and methods of thinking mapping, as well as the interaction between the two approaches in their role in learning arts. This study used experimental methods and a 2x2 factorial design to conduct quantitative research. All Junior High School second-grade pupils use the population. The analysis technique used is a two-way variant (two-way ANOVA). Student learning outcomes utilizing a demonstration technique are better than student learning outcomes using the mind monitoring method, according to the results of data processing. Students who use the demonstration approach perform better than those who use the mind mapping method. The average score for learning activeness with high demonstration methods and employing the approach of mapping student activeness thinking is poor.